Libertà di scelta della terapia e violenza medica. Brevi considerazioni sul rifiuto delle trasfusioni di sangue dei Testimoni di Geova (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. - Il “caso Oneda” - 2. -Evoluzione successiva e stato attuale - 3. - La violenza medica - 4. Conclusioni - Appendice.Freedom of choice of therapy and medical violence. Brief Considerations on the Refusal of Blood Transfusions by Jehovah's WitnessesABSTRACT: This short essay considers the change in the jurisprudential orientation on the matter in the light of the recent regulatory and healthcare evolution. In Italy the debate began with the Oneda case, which saw the conviction of two parents who opposed the transfusions of their daughter - at the time the only known therapy to combat a severe form of anemia. Nowadays, this question must be contextualized in the light both of the principle of health self-determination and the possibility of the "bloodless" treatment. Therefore, the Court of Tivoli (the sentence is attached in appendix) recently convicted a doctor who transfused a dissenting patient for “private violence”.